ANALISIS BERBASIS SIMULASI TERHADAP SIFAT AERODINAMIKA AIRFOIL NACA 2412 DENGAN PENAMBAHAN ELEMEN FLAP DAN SLAT - Okto Dinaryanto; Bahrul Jalaali; Syahrizal; Abdul Haris Subarjo; Dedet Hermawan Setiabudi; Eli Kumolosari (Mechanical Engineering Department, Faculty of Engineering, Universitas Lambung Mangkurat, 2025)
The original concept for the Easy-Fly project was to create an ultra-light STOL (Short Takeoff and Landing) plane featuring minimal drag and speed attributes. To support this goal, CFD (Computational Fluid Dynamics) was applied by varying the configuration of single-grooved flaps and slats and the angle of attack on the NACA 2412 airfoil. The viscous model used in this case is Spalart-Allmaras. The variation of the angle of attack (α) was modified in the range of 0°-20°. For the flap model, the deflection angle was adjusted to 30° and 40°, and slats were added to the configuration. Based on the results of the study, it was found that flap deflections of 30° and 40° resulted in higher CL values ​​at an angle of attack of 0°. The use of flap and slat designs on the NACA 2412 airfoil effectively delayed airflow separation until it reached a maximum angle of attack of 24°. In addition to the high-lift system design on the NACA 2412 airfoil, changes in camber and effective chord line adjustments resulted in significant improvements in the lift coefficient (CL), drag coefficient (CD), and stall angle. Finally, a 30° flap deflection was more efficient than a 40° deflection in takeoff conditions. The average percentage increase in CL/CD from a 30° to a 40° flap was 17.61%.